The impact and efficacy of routine pulse oximetry screening for CHD in a local hospital. (24th February 2016) - Jones, Andrew J.; Howarth, Claire; Nicholl, Richard; Mat-Ali, Ezam; Knowles, Rachel
Abstract: Objectives: The objective of this study was to evaluate the impact and efficacy of pulse oximetry screening for CHD in a level-two neonatal unit without on-site access to paediatric echocardiography. Methods: All neonatal unit admissions between 1 September, 2011 and 31 August, 2013 were reviewed to determine the outcomes of newborns identified by pulse oximetry screening. Record linkage with the National Congenital Heart Disease Audit allowed follow-up of newborns with a negative screening result. Results: There were 11, 233 live births during the study period, with 973 neonatal unit admissions unrelated to pulse oximetry screening. From the remaining screening population of 10, 260 newborns, 23 were admitted on the basis of a screen-positive result; three of the 23 patients went on to have urgent echocardiograms, and two were found to have critical CHD. In the 21 newborns without critical CHD, an alternative diagnosis was made in 16 cases. Record linkage with the National Congenital Heart Disease Audit indicated that no newborns born in the hospital during the study period received surgery for critical CHD following negative screening. The estimated sensitivity of screening was 100% (95% confidence interval 15.81–100%) and specificity was 99.80% (95% confidence interval 99.69–99.87%), with a false-positive rate of 0.20% (95% confidence interval 0.13–0.31%). Conclusion: The introduction of pulse oximetry screening to a hospital where paediatric echocardiography services are not available is practical, results in very few referrals to the regional paediatric cardiology centre, and detects cases of CHD that would otherwise go undiagnosed. Record linkage with a national CHD database provides a straightforward method for tracking cases of CHD that may have been missed by screening.